PENINGKATAN PEMAHAMAN SISWA TERHADAP TEKS EKSPOSISI DALAM MEDIA MASA MELALUI ADVANCE ORGANIZER DI SMPN - Masrik, H . (Universitas Tanjungpura, 2019)
The object of the authors of this Scientific paper study is based on the fact thatstudents' understanding of the Exposition Text material is still low. In fact, bymastering of Indonesian language in general, the students do not experiencedifficulties in learning other subjects. This observation was carried out in Januaryto May 2017, because in those months the students had finished the general testand were at the end of the semester so that the condition of the students could be observed from the beginning. The Advance Organizer teaching model is one of the models in the information processing family developed by David Ausubel (1963). From this writing, it can be concluded that the existence of motivation in Advance Organizing learning the ability of students towards Exposition Text material and learning outcomes will be optimal. The more precise the motivation provided, the more successful the lesson will be. With high motivation, the intensity of student learning efforts. It will be able to increase students' understanding of the Exposition Text material in the media through the advance organizer. Keywords: Improvement, Exposition Text Material, Mass Media, Advance Organizer